Isak Niehaus, witchcraft and a life in the new South Africa - Du Plooy, S. (University of the Free State, 2014)
Abstract not available
Isak Niehaus, Witchcraft and a life in the new South Africa. Cambridge: Cambridge University Press, 2013; xxiii + 239 pages; ISBN 978-1-101-65600-0 (African Paperback edition)
Keywords: Witchcraft and a life in the new South Africa; Niehaus, Isak; Witchcraft; Mohale, Jimmy; Book review